2017
DOI: 10.3892/ol.2017.6716
|View full text |Cite
|
Sign up to set email alerts
|

NHE1 has a notable role in metastasis and drug resistance of T-cell acute lymphoblastic leukemia

Abstract: Abstract. T-cell acute lymphoblastic leukemia (T-ALL) represents a spectrum of hematological malignancies that affect human health. Metastasis and chemotherapeutic drug resistance are the primary causes of mortality in patients with T-ALL. Sodium-hydrogen antiporter 1 (NHE1) is established to serve a role in metastasis and drug resistance in numerous types of cancer; however, the function of NHE1 in T-ALL remains to be elucidated. Previously, the C-C-motif chemokine ligand 25 (CCL25) was identified to be invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Taken together, our analysis (>1000 glioma cases) strongly suggests that NHE1 protein is involved in glioma tumorigenesis and progression. The underlying mechanisms could include promoting tumor proliferation and invasion [ 37 41 ]. Our gene ontology analysis indicates that NHE1 protein is involved in the tumor migration and invasion by the regulation of cell adhesion and extracellular matrix organization.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, our analysis (>1000 glioma cases) strongly suggests that NHE1 protein is involved in glioma tumorigenesis and progression. The underlying mechanisms could include promoting tumor proliferation and invasion [ 37 41 ]. Our gene ontology analysis indicates that NHE1 protein is involved in the tumor migration and invasion by the regulation of cell adhesion and extracellular matrix organization.…”
Section: Discussionmentioning
confidence: 99%
“…In T-cell acute lymphoblastic leukemia cells, ERM phosphorylation has been found to promote invasion [51], and EZR deregulation has been related to the progression of mouse preleukemia erythroblasts toward malignancy [52]. In acute myeloid leukemia cells, functional studies have shown that EZR promotes survival and acts as an effector protein in cell signaling mediated by FLT3-ITD and mutated KIT receptors [52][53][54].…”
Section: Leukemiamentioning
confidence: 99%
“…in the microenvironment plays an immunosuppressive role and mediates the protonation of drugs, affecting their cell permeability (Altaf et al, 2017;de la Cruz-López et al, 2019). In T-ALL, increased NHE1 activity may promote resistance to DOX and imatinib (Man et al, 2014).…”
Section: Acidificationmentioning
confidence: 99%